Glucocorticoid‐related changes in body mass index among children and adolescents with rheumatic diseases. Issue 1 (27th December 2012) - Shiff, Natalie J.; Brant, Rollin; Guzman, Jaime; Cabral, David A.; Huber, Adam M.; Miettunen, PaiviMm.; Roth, Johannes; Scuccimarri, Rosie; Alos, Nathalie; Atkinson, Stephanie A.; Collet, Jean Paul; Couch, Robert; et al.
Abstract Objective To examine the temporal and dose‐related effects of glucocorticoids (GCs) on body mass index (BMI) in children with rheumatic diseases. Methods Children initiating GCs for a rheumatic disease (n = 130) were assessed every 3 months for 18 months. BMI, weight, and height Z score trajectories were described according to GC starting dosage in prednisone equivalents: high (≥1.0 mg/kg/day), low (<0.2 mg/kg/day to a maximum of 7.5 mg/day), and moderate (between high and low) dosage. The impact of GC dosing, underlying diagnosis, pubertal status, physical activity, and disease activity on BMI Z scores and on percent body fat was assessed with longitudinal mixed‐effects growth curve models. Results The GC starting dose was high in 59% and moderate in 39% of patients. The peak BMI Z score was +1.29 at 4 months with high‐dose GCs and +0.69 at 4.2 months with moderate‐dose GCs (P < 0.001). Overall, 50% (95% confidence interval 41–59%) of the children returned to within +0.25 SD of their baseline BMI Z score. Oral GC dose over the preceding 3 months was the most significant determinant of BMI Z score and percent body fat. The proportion of days in receipt of GCs, disease activity, and a diagnosis of systemic‐onset juvenile idiopathic arthritis were also associated with BMI Z scores. The correlation between changes in BMI and changes in percent body fat was 0.09. Conclusion In children with rheumatic diseases starting moderate and high doses of GCs, BMI Z scores peaked at 4 months, and only half returned to within +0.25 SD of their baseline BMI Z score after 18 months.